2009
DOI: 10.1111/j.1365-2230.2008.03182.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous CD30+ anaplastic large-cell lymphoma with generalized skin involvement and involvement of one peripheral lymph node, successfully treated with low-dose oral etoposide

Abstract: Primary cutaneous CD30+ anaplastic large-cell lymphoma (PCALCL) in adults is rare, and the prognosis is generally excellent. Multifocal PCALCL tends to relapse after multiagent chemotherapy and is generally considered more prone to progress to extracutaneous involvement than is the localized disease. We report a 43-year-old woman with PCALCL who had generalized skin involvement accompanied by involvement of one peripheral draining lymph-node region. Although the disease relapsed after multiagent chemotherapy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Moreover, relapses are common and continued or repeated maintenance treatment is often required. Apart from MTX, anecdotal case reports and small series suggest that etoposide, vinblastine and retinoids (bexarotene, acitretin and isotretinoin) alone, or in combination with interferon alpha may represent alternative effective and well‐tolerated options for refractory multifocal C‐ALCL …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, relapses are common and continued or repeated maintenance treatment is often required. Apart from MTX, anecdotal case reports and small series suggest that etoposide, vinblastine and retinoids (bexarotene, acitretin and isotretinoin) alone, or in combination with interferon alpha may represent alternative effective and well‐tolerated options for refractory multifocal C‐ALCL …”
Section: Discussionmentioning
confidence: 99%
“…Apart from MTX, anecdotal case reports and small series suggest that etoposide, vinblastine and retinoids (bexarotene, acitretin and isotretinoin) alone, or in combination with interferon alpha may represent alternative effective and well-tolerated options for refractory multifocal C-ALCL. 7,8,[31][32][33][34][35] Recent studies report high response rates of BV in patients with primary cutaneous CD30-positive lymphoproliferations, including patients with relapsed and extracutaneous (multifocal) C-ALCL. 15,16,[18][19][20] A recent phase III trial compared the efficacy of BV in 16 patients with C-ALCL, including 12 patients with multifocal skin lesions and seven patients with extracutaneous disease, to MTX or bexarotene in 15 patients with C-ALCL including six with multifocal skin lesions and four with extracutaneous disease.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose MTX is widely used for LYP, but there are only anecdotal reports on its use in PCALCL. 38,46 Monoclonal antibodies SGN-30, a chimeric monoclonal antibody to CD30, has been used in 13 patients with PCALCL. 40,47,48 In an open-label multicenter phase 2 study, 6 of 11 (55%) patients achieved CR and 3 of 11 (27%) patients showed partial remission (PR).…”
Section: Chemotherapymentioning
confidence: 99%
“…In a recent review, there were 3 PRs and 4 CRs in the 7 cALCL cases treated with oral etoposide, 50 mg/d. 59 Etoposide remains a well-tolerated therapeutic option for refractory, multifocal cALCL.…”
Section: Etoposidementioning
confidence: 99%